Warlord Hitler : with reference to the campaign in southern Russia in 1942 - Donohue, Alan (2024)
"This book is a study of Adolf Hitler in his role as military commander and strategist from the beginning of the Second World War until the end of 1942, examining in detail the campaign in southern Russia that year. Warlord Hitler will appeal to postgraduates and specialists in military history, as well as general readers interested in a deeper study of the Second World War